Time Management in Nepal with Reference to Middle Level Public Sector Managers-Dinesh Raj Sharma - Kandel, Hari Datta (Administration and Management Review, 2009)
Not Available. Administration and Management Review Vol. 20, No. 1, January, 2008, Page 59-62